IMPACT OF NUTRITIONAL GUIDANCE ON LIPID LEVELS AFTER LIPOSUCTION - Durdana Inayat; Mehwish; Mamoona Shaikh; Muhammad Amjad Kalhoro; Noor Jehan Memon; Bedarbakhat Khan (Journal of Population Therapeutics and Clinical Pharmacology, 2024)
Objective: To investigate how dietary advice affects the control of weight after liposuction.Study design: A case-control studyPlace and Duration: This study was conducted in CH Fazal Din Welfare Trust Hospital Faisalabad road Okara from January 2019 to January 2020Methodology: This study included 200 adult participants of both genders undergoing liposuction and/or abdominoplasty, monitored for three months postoperatively. Participants were divided into two groups: Group A, which received dietary counseling and diet plans, and Group B, which did not receive any dietary advice. Lipid profiles were measured at baseline and three months after the procedure. Data analysis was performed using SPSS version 20.Results: Of the 200 participants, 166 (83%) completed the study: 86 (51.8%) in Group A and 80 (48.2%) in Group B. The cohort comprised 38 (22.9%) males and 128 (77.1%) females, with 110 (66.3%) under 40 years of age and 56 (33.7%) aged 40 years or older. Both groups showed significant intra-group improvements in total cholesterol, LDL, and triglycerides (p0.05). In Group A, HDL levels dramatically increased, but in Group B, they significantly fell (p0.05), with the exception of total cholesterol (p